NILAI-NILAI PENDIDIKAN KARAKTER DI PONDOK PESANTREN BAHRUL ULUM TAMBAKBERAS JOMBANG - Ali - Mutaqqin (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2018)
Character education is essentially a virtue value education that aims to shape the character ofstudents so that they are dignified and noble. Islamic boarding schools are a nationaleducation subsystem that has been developing for along time and has proven successful ineducating santri to have noble character. The success of Islamic boarding schol in educatingtheir santri characters because Islamic boarding schools have a number of character valuesinstilled in their students by using strategies and methods comprehensively. This studyexamines the value of character education in Bahrul Ulum Islamic boarding school inTambakberas Jombang. This study uses a qualitative approach that aims to describe thesubject of research phenomenologically. The results of this study are that the values ofcharacter education instilled in Bahrul Ulum Islamic boarding school are 10 items, namely:faithful, honesty, sincerity, obedience and respect, simplicity, brotherhood independence,love in science, freedom and leadership. These character of values are a yardstick for thegoodness of someone who must be manifested in the mind, attitude and behavior in relationto God, itself, family, society, nation people, and natural environment.